2012
DOI: 10.1186/1745-6215-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved clinical outcome after invasive management of patients with recent myocardial infarction and proven myocardial viability: primary results of a randomized controlled trial (VIAMI-trial)

Abstract: BackgroundPatients with ST-elevation myocardial infarction (STEMI) not treated with primary or rescue percutaneous coronary intervention (PCI) are at risk for recurrent ischemia, especially when viability in the infarct-area is present. Therefore, an invasive strategy with PCI of the infarct-related coronary artery in patients with viability would reduce the occurrence of a composite end point of death, reinfarction, or unstable angina (UA).MethodsPatients admitted with an (sub)acute myocardial infarction, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 30 publications
1
117
0
Order By: Relevance
“…Furthermore, with this sample size we were unable to analyze clinical end-points. However, recently published results of the VIAMI-trial, which included stable patients with acute MI not treated with primary or rescue PCI and with viability by dobutamine echocardiography, demonstrated that PCI after at least 48 h improved outcomes in comparison to conservative strategy [27]. Our findings suggest that the improved event-free survival observed with late PCI of an IRA in the VIAMI-trial may be the consequence of an improved LV systolic performance and size.…”
Section: Limitations Of the Studymentioning
confidence: 55%
“…Furthermore, with this sample size we were unable to analyze clinical end-points. However, recently published results of the VIAMI-trial, which included stable patients with acute MI not treated with primary or rescue PCI and with viability by dobutamine echocardiography, demonstrated that PCI after at least 48 h improved outcomes in comparison to conservative strategy [27]. Our findings suggest that the improved event-free survival observed with late PCI of an IRA in the VIAMI-trial may be the consequence of an improved LV systolic performance and size.…”
Section: Limitations Of the Studymentioning
confidence: 55%
“…The correlation between IPV exposure and lower resilience may be linked to compromised parenting ability of one or both caregivers in the context of intra-couple violence (Holt et al, 2008). This may be especially true in Uganda, as the majority of IPV is men’s perpetration of violence against women, and women also take on the majority of the caretaking responsibilities (Abramsky et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…An invasive approach in patients with a high viability score had a substantial reduction in ischemic events. the VIAMI-trial supports the concept that viability determines prognosis 17 .…”
Section: Prognostic Valuementioning
confidence: 60%